The teaching of Jesus - M. Rasi, Humberto (2013)
There is a general consensus that, despite his brief ministry, Jesus was the master of greater impact and influence in the history of mankind. It is natural thatChristian educators wishing to learn from his teaching and apply, as far as possible to their own teaching practice. This article first analyzes the differences between training, personality and the environment in which Jesus performed his work and the educational context of our contemporary reality. Then he outlined the four models that already existed within the Greek and Hebrew culture, for teachers of his time, but that Jesus did not imitate. Then examines the characteristics of his teaching style. At the core of the paper studies and exemplify seven teaching methods employed by Jesus, who contributed to the success of his mission.